SANKSI ADAT TERHADAP ANGGOTA KAN YANG MENGUASAI TANAH ULAYAT NAGARI TANPA HAK DI NAGARI SIRUKAM KECAMATAN PAYUNG SEKAKI KABUPATEN SOLOK - Indah Widyawati, Joni Zulhendra dan (Normative Jurnal Ilmiah Hukum, 2025)
Customary sanctions against members of the KAN (Nagari Customary Council) Sirukam who illegally control communal land in Nagari Sirukam, Payung Sekaki District, Solok Regency: Land that was considered property rights is returned to nagari land, and the physical ownership letter is revoked and declared invalid. Members of the Nagari Customary Council (KAN) are dismissed and an Interim Replacement (PAW) is proposed. They are dismissed from their positions as niniak mamak and returned to their respective tribes. They are not permitted to bring sahilie samudiak into the nagari until they have paid a fine. Finally, they are ostracized from the Nagari Sirukami customary environment. The process of imposing customary sanctions on members of the KAN (Nagari Customary Council) who illegally control communal land in Nagari Sirukam, Payung Sekaki District, Solok Regency: Members of the Nagari Customary Council (KAN) who illegally control communal land are summoned for questioning at the customary hall